2016
DOI: 10.1016/j.forsciint.2016.08.013
|View full text |Cite
|
Sign up to set email alerts
|

An overview of emerging and new psychoactive substances in the United Kingdom

Abstract: The purpose of this review is to identify emerging or new psychoactive substances (NPS) by undertaking an online survey of the UK NPS market and to gather any data from online drug fora and published literature. Drugs from four main classes of NPS were identified: psychostimulants, dissociative anaesthetics, hallucinogens (phenylalkylamine-based and lysergamide-based materials) and finally benzodiazepines. For inclusion in the review the 'user reviews' on drugs fora were selected based on whether or not the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 28 publications
0
38
0
Order By: Relevance
“…[11,13] Since methylphenidate is a widely regulated pharmaceutical, structurally diverse and often more potent NPS of the phenidate class have entered the drug market. [14,15] Molecular structures and the respective activities at the DAT have been reported for many of these compounds in the scientific literature, thus making the targeted synthesis of potent phenidate analogs for the drug market likely. [16] Phenidates were also recently seized by…”
Section: Introductionmentioning
confidence: 99%
“…[11,13] Since methylphenidate is a widely regulated pharmaceutical, structurally diverse and often more potent NPS of the phenidate class have entered the drug market. [14,15] Molecular structures and the respective activities at the DAT have been reported for many of these compounds in the scientific literature, thus making the targeted synthesis of potent phenidate analogs for the drug market likely. [16] Phenidates were also recently seized by…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that reasons and motivations for different types of NPS use can vary considerably . These studies indicate that use of novel stimulants and hallucinogens is mainly motivated by self‐exploration, facilitation of social situations, euphoria ( get high ) and insignificantly associated with dependency.…”
Section: Discussionmentioning
confidence: 98%
“…Drugs include cocaine (crack), MDMA (ecstasy), hallucinogenics, methamphetamine (crystal meth), and Toradol (Ketorolac), in addition to several hallucinogenic drugs and entheogen which are not limited to LSD (acid), NBOMe (n-bomb), and Dimethyltryptamine (DMT) (Beharry & Gibbons, 2016). Stimulants (as in cocaine) and hallucinogens act via increasing the levels of serotonin mainly by working on SERT located centrally (CNS) (Blough et al, 2014).…”
Section: Case Discussionmentioning
confidence: 99%